Slave away or get away: Escape rooms as a motivational tool for the CLIL history classroom in higher education - Lucía Bellés-Calvera (Universidad de La Sabana, 2022)
In present-day educational contexts, the integration of Information and Communication Technologies (ICTs) and gamification have been the basis for the implementation of escape rooms as pedagogical tools (Brusi & Cornellà, 2020; Rutledge et al., 2018). This paper aims at examining the role of virtual escape rooms in boosting History learners' motivation in Content and Language Integrated Learning (CLIL) contexts. Twenty-nine first-year undergraduates enrolled in a Classical History module delivered at a Spanish university have taken part in this study by participating in a virtual escape room and answering a final survey. The findings reveal that escape rooms may result in highly-motivated students who feel less pressure when communicating in the target language. The implementation of escape rooms can therefore be seen as a useful resource in e-learning environments, fostering oral, collaborative and critical thinking skills.